Intensive cultivation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
My, how they pack them in in South Africa! With 107 presentations in two days, plus poster sessions, bringing together a total of 140 papers, the agroforestry community of southern Africa brought itself up to date at its packed workshop on...